The future of worldwide income distribution - Tomáš Hellebrandt; Paolo Mauro (Luxembourg Income Study (LIS), 2015)
Combining consensus forecasts of growth of population and real incomes during 2014-35 with household income surveys for more than a hundred countries accounting for the bulk of the world economy, we project the income distribution in 2035 across all individuals in the world. We find that the Gini coefficient of global inequality declined from 69 in 2003 to 65 in 2013, and we project that it will decline further to 61 in 2035, largely owing to rapid economic growth in the emerging-market economies. We project major increases in the potential pool of consumers worldwide, with the largest net gains in the developing and emerging-market economies. The number of people earning between US1,144 and US3,252 per year in 2013 prices in purchasing power parity (PPP) terms will increase by around 500 million, with the largest gains in Sub-Saharan Africa and India; those earning between US3,252 and US8,874 per year in 2013 prices will increase by almost 1 billion, with the largest gains in India and Sub-Saharan Africa; and those earning more than US8,874 per year will increase by 1.2 billion, with the largest gains in China and the advanced economies. Using household survey data, we begin to trace the implications of these results for consumption patterns by documenting a positive, convex relationship between per capita consumption and the share of transportation in total consumption, which suggests a more rapid rise in transportation consumption than based on projected GDP growth.
Keywords: D12; D31; O47; 330; Consumption; Food; Transportation; Global Income Distribution; Growth; Population